DEVELOPMENT TREND OF INTERNATIONAL FINANCIAL CENTERS - Yu. N. Gusev (Модернизация, инновация, развитие, 2016)
Paper is devoted to the prospects of forming in Moscow an international financial center, the improvement of Russian legislation with regard to financial markets, taking into account the changes brought about by the global crisis, the formation of a coordinated system of regulatingfinancial markets, assessing the feasibility of establishing a single federal agency overseeing banks, insurance companies, an effective the judiciary; intensification of monetary and financial cooperation with leading foreign trade partners of Russia.